Taxonomic remarks on the genus Ctenodrilus (Annelida: Cirratulidae) including description of a new species from the Pacific Ocean - Magalhães, Wagner F.; Weidhase, Michael; Schulze, Anja; Bailey-Brock, Julie H. (Zootaxa, 2016)
A new species of Ctenodrilus is described based on morphology, anatomy and molecular (COI and 16S) data. Phylogenetic analyses revealed that the newly described Hawaiian species is the sister taxon of the widely distributed C. serratus. Comparisons of K2P distances show distances of at least 10.9 % for 16S and 18.7 % for CO1. Morphology of C. serratus differs from C. pacificus sp. nov. in the shape, number and distribution of multidentate hooks along the body, extent in segments of anterior ventral cilia, and presence of stomach cilia. Ctenodrilus pacificus sp. nov. resembles C. parvulus in terms of the internal anatomy but differs in respect to the shape of multidentate hooks. Asexual reproduction in the new species is described including associated changes in the external morphology and internal anatomy. A revision of the taxonomic characters of Ctenodrilus is also presented in order to provide background information for a better assessment of the widely distributed taxon Ctenodrilus serratus.